Community-based Participatory Healthy Lifestyle Strategies in Kedungwungu Village, Binangun District, Blitar Regency - Rodiah Astuti; Sri Utami; Septiana Hariyani (Program Pascasarjana Universitas Brawijaya, 2019)
Kedungwungu Village is one of the villages in Binangun District, Blitar Regency, East Java Province in which the people generally have not applied ODF (Open Defection Free) or, in other words, still defecate carelessly. This research aimed to formulate community-based participatory healthy lifestyle strategies in Kedungwungu Village, Binangun District, Blitar Regency. This research used a descriptive-quantitative approach, in which the number of respondent samples used was calculated using the Solvin formula with an error rate of 10%. As for formulating community-based participatory healthy lifestyle strategies in Kedungwungu Village, the researcher analyzed the questionnaire results using a SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis method. With this method used, 110 respondents were obtained from the total Kedungwungu Village’s population of 3,399 people. The SWOT analysis found that some formulations of community-based participatory healthy lifestyle strategies for the people of Kedungwungu Village include socializing the criteria for clean water and water as one of the mediums that can spread diseases, carrying out sustainable water management, conducting a clean village program at least once a month to keep the village clean and healthy, socializing the criteria for healthy latrines and healthy latrine programs to each house, and providing facilities in the form of healthy latrines around the agricultural area so that farmers and the public do not defecate carelessly.Keywords: participatory, healthy lifestyle, strategy